Gamified e-Commerce A New Paradigm on e-Media Business - Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2012)
Nowadays, e-commerce and e-business have increasingly become a necessary component of business strategy. It’s also become a strong catalyst for economic development. We can see it through the report given by various authors [1, 2, 3]. Gamification, on the other hand, is a new term used to describe the using of game elements and game design techniques in other non-game areas/activities, such as business, education, health, politics, etc [4]. Gamification studies and improvements also take place on the e-commerce fields, as we can see on some e-commerce sites, such as ebay, foursquare, amazon gold box, and salesforce.com which has implement the gamification concept on their sites. On this paper, we will explore this new paradigm on e-media business: the usage of gamification concept on e-commerce field. Is it possible? What are the advantages? And what are the disadvantages? All this questions lead us to the new term known as GE-commerce (Gamified E-commerce). Index Terms—e-commerce, gamification, business strategy, ge-commerce